Roman Imperial Titulature and Chronology, A.D. 235-284 - Peachin, M. (Classical Studies - Book Archive pre-2000., 1989)
Peachin, M. Roman Imperial Titulature and Chronology, A.D. 235-284. 1989 This study is a basic work of reference for the history of the Roman Empire during the midthird century A.D. The book consists of two principal parts. Part two, upon which the first is based, is a catalogue that lists all known variants of the titulature of each emperor from this period. In turn, each variant is accompanied by a list of all attestations (including coins, inscriptions, papyri) of that formula. An introduction traces briefly the historical development of the official titular formula, and then discusses the method of granting this formula at the beginning of the period in question. The introduction is followed by a chapter that evaluates the source material. Given a secure basic understanding of how the ancient testimonia are to be employed, the book then progresses to a chapter that sets out a complete chronology for the period. SA 29 (1989), 543 p. Cloth. 21x28 cm. - 118.00 EURO, ISBN: 9050630340